The use of multimedia in biology learning: MAS Subulussalam Sumberjo student responses - Cici Julianti; Risma Delima Harahap; Islamiani Safitri (Master Program of Biology Education, Universitas Lambung Mangkurat, Banjarmasin, Indonesia, 2022)
The use of the lecture method in learning biology in the classroom does not provide opportunities for students to develop skills and express their opinions. Multimedia learning media is needed to increase the interest and quality of student learning. This study uses a qualitative method. The subjects of this study were 44 students of MAS Subulussalam Sumberjo, Torgamba District, South Labuhanbatu. The focus of this research is on students of class X MIPA-A and X MIPA-B, and the results obtained are in the form of observation data, interviews and questionnaires to determine student responses to the use of multimedia in learning biology. Indicators that are used as a reference to see student responses to the use of multimedia are learning with the lecture method, the implementation of multimedia learning in the form of animated videos, the quality of multimedia presentation, and the effect of using multimedia in the form of animated videos. In conclusion, the learning indicator using animated video media has a large percentage value compared to the number of other indicators, namely 90%, so that student reactions can be interpreted as follows: The use of multimedia is very good, because the use of multimedia makes students more active and enthusiastic in learning biology.Abstrak Penggunaan metode ceramah dalam pembelajaran biologi di kelas tidak memberikan kesempatan kepada siswa untuk mengembangkan keterampilan dan mengemukakan pendapatnya. Media pembelajaran multimedia dibutuhkan untuk meningkatkan minat dan kualitas belajar siswa. Penelitian ini menggunakan metode kualitatif. Subjek penelitian ini adalah 44 siswa MAS Subulussalam Sumberjo Kecamatan Torgamba Labuhanbatu Selatan. Fokus penelitian ini pada siswa kelas X MIPA-A dan X MIPA-B, dan hasil yang diperoleh berupa data observasi, wawancara dan angket untuk mengetahui respon siswa terhadap penggunaan multimedia dalam pembelajaran biologi. Indikator yang dijadikan acuan untuk melihat tanggapan siswa terhadap penggunaan multimedia adalah pembelajaran dengan metode ceramah, pelaksanaan pembelajaran multimedia dalam bentuk video animasi, kualitas penyajian multimedia, dan pengaruh penggunaan multimedia dalam bentuk video Animasi. Kesimpulannya, indikator pembelajaran dengan media video animasi memiliki nilai persentase yang besar dibandingkan dengan jumlah indikator lainnya yaitu 90%, sehingga reaksi siswa dapat diartikan sebagai berikut: Penggunaan multimedia sangat baik, karena penggunaan multimedia membuat siswa lebih aktif dan bersemangat dalam pembelajaran biologi.